East or West: Revisiting Marrtyrdom in the Qur'an - Amin, Elsayed Mohamed Abdalla; Aljahsh, Muhammad Ahmad Ibrahim (Islam Transformatif : Journal of Islamic Studies, 2023)
AbstractThis study tackles the underexplored concept of â€˜Istishhadâ€™(martyrdom) in Sunni Qurâ€™anic commentaries, comparing the classical commentaries with the modern ones. It undertakes a thorough content analysis of classical interpretations of al-Qurá¹ubi and al-Razi with contemporary interpretations from the late nineteenth century by Rashid Riá¸a and al-Shaâ€˜rawi enabling critical and comparative analysis of these diverse interpretations to capture the evolution of the term Istishhad throughout history. It finds prevalent misunderstanding(s) and misrepresentation(s) of martyrdomin some modern Western literature, underscoring the urgency for more accurate and nuanced comprehension in modern religious and geopolitical dialogues. The study contributes to how a sound and diverse understanding of 'istishhad'as arrived at by the consulted classical and modern interpretations can potentially solve some modern socio-cultural dynamics within and beyond Muslim societies. Significantly, it shows how the concept of 'istishhad' as understood or practiced can influence global religious views about Islam within the realm of socio-political discourse. Finally, the study advocates for the incorporation of a broader array of Islamic perspectives in future scholarly work, moving beyond mainstream Sunni interpretations of the Qurâ€™an to find complementary interpretations in the Prophetic Sunnah.Â Penelitian ini menyelidiki konsep 'Istishhad' (kesyahidan) yang belum banyak diteliti dalam tafsir al-Qurâ€™an Sunni, dengan membandingkan tafsir klasik dan modern. Melalui analisis konten yang mendalam terhadap interpretasi klasik oleh al-Qurá¹ubi dan al-Razi, serta interpretasi kontemporer oleh Rashid Riá¸a dan al-Sha'rawi dari akhir abad ke-19, penelitian ini memungkinkan analisis kritis dan komparatif terhadap berbagai interpretasi tersebut untuk mengungkap evolusi istilah Istishhad sepanjang sejarah. Penelitian ini mengidentifikasi kesalahpahaman dan representasi yang keliru tentang kesyahidan dalam beberapa literatur Barat modern, menekankan pentingnya pemahaman yang lebih akurat dan berdimensi dalam dialog agama dan geopolitik kontemporer. Kontribusi penelitian ini terletak pada bagaimana pemahaman yang komprehensif dan beragam tentang 'istishhad', yang dihasilkan dari interpretasi klasik dan modern yang dianalisis, dapat membantu mengatasi beberapa dinamika sosial-budaya kontemporer, baik di dalam maupun di luar masyarakat Muslim. Secara signifikan, temuan ini menunjukkan bagaimana konsep 'istishhad', baik dalam pemahaman maupun praktiknya, dapat mempengaruhi persepsi global terhadap Islam dalam diskursus sosial-politik. Penelitian ini mengakhiri dengan merekomendasikan inklusi perspektif Islam yang lebih luas dalam studi ilmiah mendatang, melewati batasan interpretasi Sunni mainstream al-Qurâ€™an untuk mengeksplorasi interpretasi pelengkap dalam Sunnah Nabi.